Analisis Faktor – Faktor yang Mempengaruhi Pendapatan Sopir Batu Belig Transport Di Kelurahan Kerobokan Kelod - Bere, Fransiscus Xaverius Suryadana; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Needed for high mobility has increased the demand for modes of transportation so that many people start working in the field. Increasing the role of drivers will also affect the social and economic life. The purpose of this study is to determine the effect of working hours, age, and experience of income from Batu Belig Transport (BBT) drivers. This study uses a kind of secondary data, cross sectional, and uses a saturated sample in data collection. The analysis technique used multiple linear regression analysis. Based on the analysis results found that working hours have a positive and significant effect on the BBT driver's income, while the age has a negative and significant effect on the BBT driver's income. Work experience depicting the working period of the driver has no significant effect on the BBT driver's income. The increase of driver working hours, the greater the income, while with the age of the driver, their income will decrease. Keywords: working hours, age, experience, revenue